Advances in signal processing and intelligent recognition systems : proceedings of third International Symposium on Signal Processing and Intelligent Recognition Systems (SIRS-2017), September 13-16, 2017, Manipal, India /: proceedings of third International Symposium on Signal Processing and Intelligent Recognition Systems (SIRS-2017), September 13-16, 2017, Manipal, India. ([2018]) - Unknown
No abstract available